(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
We investigate if Malaysian listed companies engaged in financial information fraud during financial distressed after two years of US subprime mortgage crisis.We also investigate the impact of financial information fraudulence in bankruptcy prediction and misclassification errors. This study used consumer product companies listed on the main board and the timeframe is from 2011 till 2015. The Altman Z score indicates that 37 out of 133 Malaysian consumer product companies are financially distressed. Meanwhile, the M score shows that 28 out of 224observations are engaged in financial information fraudulence. However, these results are relatively low because the samples are taken from the main board and fraudulence in their financial statements might be done in lower magnitude in order to avoid sanctions by the Security Exchange Commission. Logistic regression was used to measure the predicting accuracy. The result of the overall accuracy percentage slightly improved by 0.9 after eliminating fraudulent companies. The confusion matrix result i.e. before and after the removal of financial information fraudulent companies, the misclassification errors especially type one has improved. This finding satisfied objective three, whereby one of the reasons for the deterioration in financial distress prediction is due to the upward bias of financial information fraudulence.Governments, monitoring bodies, and all those involved in an insolvency process would benefit from this study.